2018
DOI: 10.1158/1078-0432.ccr-17-1983
|View full text |Cite
|
Sign up to set email alerts
|

Dual mTOR Kinase Inhibitor MLN0128 Sensitizes HR+/HER2+ Breast Cancer Patient-Derived Xenografts to Trastuzumab or Fulvestrant

Abstract: Purpose: Therapeutic strategies against hormonal receptorpositive (HR þ

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 48 publications
6
40
0
Order By: Relevance
“…Also, single cell preparations exhibited variation of ER and RB expression which is expected due to the heterogeneity in the tumor (Figure 5B ). This observation also agreed with the IHC staining of this PDX which is approximately 40-50% ER+ [ 37 ]. Moreover, as ER coverage reads increased, there is no correlation with the RB expression; thus, ER and RB are two independent factors in the cell cycle (Figure 5B ).…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Also, single cell preparations exhibited variation of ER and RB expression which is expected due to the heterogeneity in the tumor (Figure 5B ). This observation also agreed with the IHC staining of this PDX which is approximately 40-50% ER+ [ 37 ]. Moreover, as ER coverage reads increased, there is no correlation with the RB expression; thus, ER and RB are two independent factors in the cell cycle (Figure 5B ).…”
Section: Resultssupporting
confidence: 87%
“…COH-SC31, generated in our laboratory, is a unique PDX tumor model. While it is triple positive (ER/PR/HER2), it is also Herceptin resistant; thus, it completely depends on estrogen for growth [ 37 ]. Thus, this is a relevant model to demonstrate the molecular action of palbociclib because it depends on activated ER for growth, although it is HER2-positive.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reported results revealed that apart from standard trastuzumab therapies, the combination with the dual mammalian target of rapamycin (mTOR) complex inhibitor impeded tumor growth. Thus, this study opens the door for personalized medicine clinical trials (101).…”
Section: Main Type Of Protein Array Methods Analytical/antibody/indirementioning
confidence: 85%